2017
DOI: 10.1152/japplphysiol.00367.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium nitrite on local control of contracting skeletal muscle microvascular oxygen pressure in healthy rats

Abstract: Ischemic conditions as diverse as chronic heart failure (CHF) and frostbite inflict tissue damage via inadequate O delivery. Herein we demonstrate that direct application of sodium nitrite enhances the O supply-O demand relationship, raising microvascular O pressure in healthy skeletal muscle. This therapeutic action of nitrite-derived nitric oxide occurred without inducing systemic hypotension and has the potential to relieve focal ischemia and preserve tissue vitality by enhancing O delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated augmented blood flow and elevated PO 2 mv utilizing exogenous nitric oxide donors such as sodium nitroprusside and nitrate/nitrite supplementation in health and disease (Colburn et al . 2017, Craig et al . 2018, 2019 b , Ferguson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated augmented blood flow and elevated PO 2 mv utilizing exogenous nitric oxide donors such as sodium nitroprusside and nitrate/nitrite supplementation in health and disease (Colburn et al . 2017, Craig et al . 2018, 2019 b , Ferguson et al .…”
Section: Discussionmentioning
confidence: 99%
“…This reduced NO bioavailability to the upstream resistance vasculature is believed to be the primary cause of stopped capillaries and compromised muscle P O 2mv and D O 2 m in HF (Ferreira et al 2006;Hirai et al 2015), but whether increasing NO bioavailability exogenously re-establishes RBC flux in stopped capillaries in HF remains to be conclusively resolved. Notwithstanding the above, targeting the NO pathway via either direct sodium nitroprusside or nitrite superfusion (Ferreira et al 2006;Colburn et al 2017), nitrite infusion (Glean et al 2015;Ferguson et al 2016a) or dietary nitrate supplementation does increaseQ and P O 2mv in contracting healthy and HF rat muscles (Ferguson et al 2013a(Ferguson et al ,b, 2015(Ferguson et al , 2016bJones et al 2016;reviewed by Hirai et al 2015;Poole, 2019). NO raises P O 2mv by not only elevatingQ O 2 , as discussed above, but also decreasingV O 2 (Larsen et al 2007).…”
Section: Alternative Nitric Oxide Pathway Therapeutic Interventions Tmentioning
confidence: 99%
“…40-45 Inorganic nitrate and nitrite improve skeletal muscle microvascular conductance during exercise 46 and increase capillary O 2 tension facilitating O 2 diffusion into muscle cells. 47 Nitrite increases mitochondrial efficiency in skeletal muscle 48 and improves insulin sensitivity and glucose uptake. 49 A recent study in human HFrEF demonstrated improvements in muscle power with acute inorganic nitrate administration.…”
Section: Pathophysiology Of Hfpefmentioning
confidence: 99%